Interruption of HBV intrauterine transmission: A clinical study - Li, Xiao-Mao (World J Gastroenterol, 2003)
AIM: To investigate the effect of hepatitis B virus (HBV) specific immunoglobin (HBIG) and lamivudine on HBV intrauterine transmission in HBsAg positive pregnant women. METHODS: Each subject in the HBIG group (56 cases) was given 200 IU HBIG intramuscularly (im.) every 4 wk from 28-week (wk) of gestation, while each subject in the lamivudine group (43 cases) received 100 mg lamivudine orally (po.) every day from 28-wk of gestation until the 30(th) day after labor. Subjects in the control group (52 cases) received no specific treatment. Blood specimens were tested for HBsAg, HBeAg, and HBV-DNA in all maternities at 28-wk of gestation, before delivery, and in their newborns 24 h before the administration of immune prophylaxis. RESULTS: Reductions of HBV DNA in both treatments were significant (P < 0.05). The rate of neonatal intrauterine HBV infection was significantly lower in HBIG group (16.1%) and lamivudine group (16.3%) compared with control group (32.7%) (P < 0.05), but there was no significant difference between HBIG group and lamivudine group (P > 0.05). No side effects were found in all the pregnant women or their newborns. CONCLUSION: The risk of HBV intrauterine infection can be effectively reduced by administration of HBIG or Lamivudine in the 3(rd) trimester of HBsAg positive pregnant women.